Authentic leadership and employees' emotional labour in the hospitality industry. Issue 2 (18th February 2020) - Wang, Zhenyuan; Xie, Yunhui
Abstract : Purpose: This study investigates the effect of authentic leadership on service employees' emotional labour strategies, surface acting and deep acting, from a human energy perspective. Design/methodology/approach: A three-wave survey was conducted in a hotel chain in China, and 347 valid responses were obtained. Mplus software was used for structural equation modelling and bootstrapping analysis. Findings: This study finds the following: authentic leadership predicts service employees' emotional labour strategies; job insecurity mediates the influence of authentic leadership on surface acting but not on deep acting; relational energy mediates both surface and deep acting; and relational energy has more negative (positive) indirect effects than job insecurity. Practical implications: The findings provide hospitality managers with insights into how to improve service employees' capacity for emotional regulation. Hospitality managers should show more authenticity, pay attention to subordinates' energy level and select and recruit candidates with positive energy traits. Hospitality organisations should encourage, select and train managers to behave as authentic leaders. Originality/value: This study links authentic leadership with service employees' emotional management in the hospitality industry. Moreover, it demonstrates the energising function of authentic leadership and introduces the new perspective of human energy to emotional labour research.